The Sedekah 2D Animation PSA - Afif Syahmie Jefri; Jessifa Joanna Mohd Supian (Journal of Computing Technologies and Creative Content, 2022)
The Public Service Announcement is a free public service announcement that creates public awareness of a social issue and encourages people to action. Charity is an Islamic financial mechanism with a wide range of features that is based on volunteerism. The value of beginning this habit at a young age may also be significant. Teenagers are less aware of charity nowadays due to a lack of information from the charity’s organization. Many organizations continue to utilize ineffective physical posters that waste money and time for youth. Because today’s youngsters are more tech-savvy, a Public Service Announcement video is the most effective way to educate and raise awareness. This research aims to create a 2D animation Public Service Announcement (PSA) about Sadaqah. The ADDIE model is used as a research instrument for the study. In comparison to the physical poster, 100 per cent of respondents agreed that the 2D public service announcement is an effective way to promote awareness. This Sadaqah 2D Public Service Announcement is intended to encourage youngsters to be more charitable and shape them into better Muslims.